2013
DOI: 10.1111/cas.12124
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of γδ T cell responses and farnesyl diphosphate synthase inhibition in tumor cells pretreated with zoledronic acid

Abstract: Summary Exposing human tumor cells to nitrogen-containing bisphosphonates (N-BPs), such as zoledronic acid (Zol), greatly increases their susceptibility to killing by γδ T cells. Based on this finding and other studies, cancer immunotherapy using γδ T cells and N-BPs has been studied in pilot clinical trials and has shown benefits. Although Zol treatment can render a wide variety of human tumor cells susceptible to γδ T cell killing, there has not been a systematic investigation to determine which types of tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 41 publications
3
41
1
Order By: Relevance
“…16 This could account for a poor pAg accumulation in these blasts upon N-BP treatment that would fail to activate Vg9Vd2 T cells. 29 We show that anti-BTN3A 20.1 mAb can sensitize N-BP-poorly sensitized primary AML blasts to Vg9Vd2T cells lysis, notably monocytic Low AML. The sensitization of these resistant blasts to Vg9Vd2 T cells lysis with anti-BTN3A 20.1 mAb points out a potential major role of this mAb to circumvent intrinsic resistance mechanisms in blasts.…”
Section: Discussionmentioning
confidence: 72%
“…16 This could account for a poor pAg accumulation in these blasts upon N-BP treatment that would fail to activate Vg9Vd2 T cells. 29 We show that anti-BTN3A 20.1 mAb can sensitize N-BP-poorly sensitized primary AML blasts to Vg9Vd2T cells lysis, notably monocytic Low AML. The sensitization of these resistant blasts to Vg9Vd2 T cells lysis with anti-BTN3A 20.1 mAb points out a potential major role of this mAb to circumvent intrinsic resistance mechanisms in blasts.…”
Section: Discussionmentioning
confidence: 72%
“…Given the heterogeneity of the stimulating ability displayed by the various CRC cell lines, we asked whether this was due to a different sensitivity of farnesyl diphosphate synthase to Zol, as reported. 34 However, non-stimulating CRC cell lines were unable to trigger efficiently gd T cell expansion, even when pre-treated with high doses of Zol; furthermore, IPP production in response to Zol, was lower in the three non-stimulating cell lines tested and they did not enhance IPP production in response to high doses of Zol, with the exception of DLD1. Thus, we further investigated any possible difference in the expression of proteins of the butyrophilin family, mainly BTN3A1 that is an essential molecule for the recognition of PAg by gd T lymphocytes, due to its B30.2-binding domain.…”
Section: Discussionmentioning
confidence: 84%
“…As it has been reported that several tumor cell lines require higher doses of Zol to exert their stimulating activity of gd T cells, 34 three low-stimulating (SW620, HCT15, DLD1) and one stimulating (LS180) CRC cell lines were pre-treated (4 h) with high doses (100 mM and 50 mM) of Zol, washed and co-cultured with purified T cells as above. As shown in Fig.…”
Section: Crc Exposed To Zol Stimulate the Expansion Of Vd2 T Cells Wimentioning
confidence: 99%
See 1 more Smart Citation
“…In all other bacteria as well as in higher eukaryotes including humans, IPP and DMAPP are generated via the mevalonate pathway that is closely regulated by the action of 3-hydroxy-3-methyl-glutaryl-CoA reductase and downstream enzymes such as farnesyl pyrophosphate synthase. Overproduction of the low bioactivity compounds IPP and DMAPP as a result of a dysregulation of the mevalonate pathway in human cells, be it in metabolically active tissues including tumor cells or through inhibition of farnesyl pyrophosphate synthase by aminobisphophonates such as zoledronate, is thought to render such cells targets of Vc9/Vd2 T cells, despite the absence of the high bioactivity metabolite HMB-PP in this context [11,[16][17][18]. Zoledronate and related drugs are therefore receiving substantial attention as Vc9/Vd2 T cellstimulating agents in vivo especially with respect to immunotherapies against advanced solid and hematological tumors [19][20][21].…”
mentioning
confidence: 99%